Total synthesis of (+)-camptothecin via an intramolecular palladium-catalyzed cyclization strategy - Chavan, Subhash P.; Pathak, Ashok B.; Kalkote, Uttam R. (Synlett, 2007)
The novel cascade intramolecular Pd-catalyzed cyclization followed by aromatization for the construction Of D ring of (+)-camptothecin as a key step is demonstrated.
Keywords: alkaloids; antitumor; cyclizations; Natural products; Palladium